2015
DOI: 10.5312/wjo.v6.i10.754
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic cellular therapy: An overview with focus on clinical trials

Abstract: In this editorial, the authors tried to evaluate the present state of cellular therapy in orthopedic field. The topics the authors try to cover include not only the clinical trials but the various research areas as well. Both the target diseases for cellular therapy and the target cells were reviewed. New methods to activate the cells were interesting to review. Most advanced clinical trials were also included because several of them have advanced to phase Ⅲ clinical trials. In the orthopedic field, there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…However, these surgeries involve important financial costs and present some significant limits such as significant post‐operative morbidity, the need for an additional invasive procedure (second site), a limited availability and a resorption that is difficult to anticipate . These limitations have induced the development of bone substitutes such as allograft, xenograft and alloplastic materials . However, these techniques produce unsatisfactory results especially regarding the lack of vascularization in the new‐formed bone .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these surgeries involve important financial costs and present some significant limits such as significant post‐operative morbidity, the need for an additional invasive procedure (second site), a limited availability and a resorption that is difficult to anticipate . These limitations have induced the development of bone substitutes such as allograft, xenograft and alloplastic materials . However, these techniques produce unsatisfactory results especially regarding the lack of vascularization in the new‐formed bone .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that the biodegradation of nacre progresses as induction of biomineralization when implanted in rodents, sheeps or humans . It has been reported that powdered nacre was totally resorbable . Kim et al demonstrated in ovariectomized (OVX)‐induced osteoporotic mouse model that water‐soluble nacreous factors can both stimulate osteoblastic bone formation and inhibit osteoclastic bone resorption.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This preliminary finding finally led to the first successful human bone marrow transplantation in 1968 1 . Since then, orthopedic diseases have been one of the earliest targets for cellular therapy, and cartilage repair was the first indication for this therapeutic approach 2 . In 1994, Lars Peterson’s group designed a study to regenerate cartilage tissue with autologous cartilage cells and showed evidence of regeneration in both animals and humans 3 .…”
Section: Overview Of Cell Types and Classificationsmentioning
confidence: 99%